High output power, narrow linewidth Brillouin fibre laser master-oscillator/power-amplifier source - Ahmad, Harith; Moghaddam, M.R.A.; Arof, Hamzah; Harun, Sulaiman Wadi (Institution of Engineering and Technology (IET), 2011)
A high output power and narrow linewidth Brillouin fibre laser source is demonstrated with an output power of 400 mW by a master-oscillator/power-amplifier system. The laser has a linewidth of 10 kHz, optical signal-to-noise ratio of 45 dB, cladding pumping power threshold of 300 mW and a tunable output from 1548.5 to 1565 nm. The slope efficiency of 1557.4 nm signal improves from 8.7 to 12% with the increase of the input signal power from -10 to 5 dBm.